2021
DOI: 10.1002/clc.23628
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of electrocardiography findings in patients with coronavirus disease 2019: A retrospective study

Abstract: Background Coronavirus disease 2019 (COVID‐19) has reached a pandemic level. Cardiac injury is not uncommon among COVID‐19 patients. We sought to describe the electrocardiographic characteristics and to identify the prognostic significance of electrocardiography (ECG) findings of patients with COVID‐19. Hypothesis ECG abnormality was associated with higher risk of death. Methods Consecutive patients with laboratory‐confirmed COVID‐19 and defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…In a retrospective study to highlight the prognostic significance of ECG in COVID, Yang et al have compared the ECG changes in survivors and nonsurvivors. 30 It was observed that the nonsurvivors had significantly higher rates of prolonged QTc interval, axis deviation, arrhythmias, ST-T changes, and an overall higher abnormal ECG score. In our study population, QTc prolongation and tachycardia were the commonest changes in the deceased.…”
Section: Discussionmentioning
confidence: 96%
“…In a retrospective study to highlight the prognostic significance of ECG in COVID, Yang et al have compared the ECG changes in survivors and nonsurvivors. 30 It was observed that the nonsurvivors had significantly higher rates of prolonged QTc interval, axis deviation, arrhythmias, ST-T changes, and an overall higher abnormal ECG score. In our study population, QTc prolongation and tachycardia were the commonest changes in the deceased.…”
Section: Discussionmentioning
confidence: 96%
“…In particular, the primary advantages of ECG in COVID-19 include its ease in use, nominal labor intensiveness, minimal COVID-19 exposure risk, and wide availability and accessibility throughout hospitals, emergency departments, and outpatient clinics. Its short-term prognostic utility in COVID-19 has previously been described [ [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] ], further supporting its clinical application in this population. In light of an ongoing pandemic, we believe that the fundamental role of ECG extends beyond its diagnostic capacity to immediately detect time-sensitive conditions to include the powerful prediction of long-term mortality in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 64%
“…Owing to its widespread availability, ease of use, and minimal cost, one such tool that has been applied for this purpose is electrocardiography (ECG). Several studies have utilized ECG to identify untoward prognostic markers in COVID-19, which include atrial fibrillation (AF)/flutter [ [11] , [12] , [13] , [14] , [15] ], right-heart strain [ 13 , 16 ], intraventricular conduction abnormalities [ 11 , 12 , [17] , [18] , [19] ], ST segment abnormalities [ [12] , [13] , [14] ], and ischemic T-wave inversions [ 11 , 17 ]. However, these investigations often included only hospitalized patients and failed to prognosticate beyond in-hospital or 30-day outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 describes the main characteristics of the 11 observational studies from the scoping review 11–20 . Seven studies (Antwi‐Amoabeng et al., Chen et al., Han et al., Kunal et al., Ray‐Acha et al., Wang et al., and Yang et al.)…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 describes the main characteristics of the 11 observational studies from the scoping review. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 Seven studies (Antwi‐Amoabeng et al., Chen et al., Han et al., Kunal et al., Ray‐Acha et al., Wang et al., and Yang et al.) aimed to characterize electrocardiogram (EKG) findings among COVID‐19 patients without a particular focus on bradycardia.…”
Section: Resultsmentioning
confidence: 99%